Analysis of Sustainable Development Aspects of The Value-Added Mineral Policy for The Raw Materials Industry of Electric Vehicle Battery Using the Analytical Hierarchy Process (AHP) Method - Majid, M. Atthar; Dalimi, Rinaldy (Future Science, 2021)
Indonesia is currently heading for a low-carbon economy transition, one of which supports this policy. Through Presidential Decree No. 55 of 2019, the Government issued the Battery-Based Electric Motor Vehicle Program. In support of this program, the Government has a policy of Increasing mineral added value or downstream program implemented since 2009 so that the production of electric vehicle batteries can be produced domestically so that the industry has added value that will affect sustainable development in the sector. There are three criteria for problems affecting mineral downstream policies to inhibit sustainable development from the electric vehicle battery raw material industry: economic, social, and Environmental. In this study, the Analytical Hierarchy Process method determines the priority order of alternative solutions to solve complex multicriteria Problems into a hierarchy. From the results of the Analytical Hierarchy Process analysis, it was concluded that to overcome downstream problems, first is Improving the Governance of Mining and National Intermediate and Downstream Industries (51%), second is Infrastructure Development and Technology Development (31%), and third is Improving Information System Data Availability and Quality (18%).